2020
DOI: 10.2147/dmso.s237362
|View full text |Cite
|
Sign up to set email alerts
|

<p>Correlation Between Diabetic Peripheral Neuropathy and Sarcopenia in Patients with Type 2 Diabetes Mellitus and Diabetic Foot Disease: A Cross-Sectional Study</p>

Abstract: Purpose: The present study was designed to determine the relationships between sarcopenia and diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (T2DM) and diabetic foot disease (DFD) respectively. Patients and Methods: A total of 1104 patients with T2DM and 257 patients with DFD were included in the study, which was designed as a cross-sectional study. Body composition was assessed using dual-energy X-ray-absorptiometry (DXA). The diagnosis of sarcopenia was based on the Baumgartne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
(50 reference statements)
2
28
2
1
Order By: Relevance
“…The possible reasons for this variation could be different study settings and different classi cation used to diagnose DPN in these studies. The prevalence of DPN found in present study was lower as compared to study conducted by Yang Q et al [19] and Qin L et al [20] in which prevalence of DPN was close to 71.0% and 80.0% respectively due to the similar reason as they used Neuropathy symptom score (NSS) and Neuropathy disability score (NDS) to assess DPN in their study population. High prevalence of DPN is a matter of concern for clinicians and public health specialists working with diabetic patients as this may lead to ulceration, amputation, life-long disability, and poor quality of life [21].…”
Section: Discussioncontrasting
confidence: 45%
“…The possible reasons for this variation could be different study settings and different classi cation used to diagnose DPN in these studies. The prevalence of DPN found in present study was lower as compared to study conducted by Yang Q et al [19] and Qin L et al [20] in which prevalence of DPN was close to 71.0% and 80.0% respectively due to the similar reason as they used Neuropathy symptom score (NSS) and Neuropathy disability score (NDS) to assess DPN in their study population. High prevalence of DPN is a matter of concern for clinicians and public health specialists working with diabetic patients as this may lead to ulceration, amputation, life-long disability, and poor quality of life [21].…”
Section: Discussioncontrasting
confidence: 45%
“…The main causes of DPN are metabolic disorders and vascular damage [ 2 ]. DPN presents as a wide spectrum of symptoms, such as sensory loss, pain, and loss of muscle mass [ 3 ]. Although nerve conduction velocity is common in DPN patients, it is not easily or reliably diagnosed in DPN [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with T2DM with an HbA1c level higher than 8.0% were three to ve times at higher risk of limited lower extremity access than those with an HbA1c level > 5.5% [14]. A cross-sectional study showed that the average HbA1c levels were 7.9% in T2DM patients without sarcopenia and 8.4% in T2DM patients with sarcopenia [15].…”
Section: Discussionmentioning
confidence: 99%